P451Optimizing the EP lab workflow in atrial fibrillation ablation - The use of Z stitch for groin access closure. (18th June 2020) - Velagic, V; Prepolec, I; Pasara, V; Pezo-Nikolic, B; Puljevic, M; Matasic, R; Krpan, M; Lovric-Bencic, M; Puljevic, D; Milicic, D
Abstract: Introduction: As catheter ablation became the standard therapy for atrial fibrillation (AF), the number of AF procedures has risen exponentially. Therefore, workflow optimization is crucial in order to meet the rising demands for EP interventions. Recently, instead of standard groin compression we have started using the "Z stitch" for introducers' removal. This novel method does not necessitate protamine administration and often lengthy manual compression. Purpose: We aim to demonstrate utilization of "Z stitch" for groin access closure in cryoballoon (CB) ablation and its impact on EP lab workflow. Methods: We have analyzed all patients having undergone CB ablation utilizing the "Z stitch" (Z group) and the last 50 consecutive CB patients who received standard groin compression (non-Z group). Procedures were performed under conscious sedation. Both femoral veins were punctured and a single introducer was placed in each vein. A single transeptal puncture was preformed guided by intracardial ultrasound and a 28 mm cryoballoon was used. A single 180 seconds freeze strategy was employed. In the past, protamine was slowly administered after ablation and at least 15 minute manual groin compression was applied until no visual bleeding could be detected. Elastic bandage was placed around both groins. Later on, the "Z stitch" was used around both introducers without the need for protamine administration, manual compression and bandage placement (Picture). The stitches were removed next morning. Results: A total of 100 consecutive patients (79% male, 61.2 ± 10.6 years old) were evaluated, 50 in both groups. There was no difference in the mean procedure duration ("skin to skin") between two groups. However, a total lab time was significantly longer in non-Z group. There was no differences in complication rates, which consisted solely of phrenic nerve palsy and groin complications. There was no AV fistula or pseudoaneurysms detected in our cohort (Table). Conclusion: Utilization of Z stitches for introduces' removal seems safe and effective way to achieve hemostasis after cryoballoon ablation. It abolishes the need for protamine administration which can cause serious advert events. Manual compression is no longer required. Consequently, EP lab workflow is improved, since the total lab time utilization per patient is significantly shortened.